Authorial Fictions and Attributions in the Ancient Mediterranean - Bonar, Chance E.; Lindenlaub, Julia D. (Mohr Siebeck, 2024)
This volume brings together scholars of ancient religion, classics, and the Near East to explore how »falsely« attributing texts functioned to situate writers in larger literary and historical conversations, as well as to influence the interpretation and reception of a text.
PublicationDate: 20240731
Keywords: Ancient Religion -- Classical Studies -- ger / g+#275; r -- capital taxation -- Religion und Staat -- Literary Theory -- book history -- Hippolytus von Rom -- Neues Testament -- Antike -- Antike Religionsgeschichte